Tauromachy and the Bull: What Remains in a Symbol in Fernán Caballero's La gaviota. - Fernández-Medina, Nicolás (Bulletin of Hispanic Studies (1475-3839), 2009)
Fernán Caballero's popular novel La gaviota has been criticized as an uneven text replete with all manner of contradictions that stem from the disjunction between the author's romantic affinities and realist ambitions. Through the art of tauromachy and its bull symbol, it is possible to trace a complex semi-private symbolism in the novel that enhances certain aspects of its realism by forging a textual 'middle space' in which contradictions like eros/thanatos, God/godless and salvation/damnation, among others, are considered dialectically. Instead of impoverishing the literary work, the contradictions contribute to the underlying structural frame of the text and the soteriological logic that sustains it.